Intervention policy of the BoJ: a unified approach - Michel Beine; Oscar Bernal; Jean-Yves Gnabo; Christelle Lecourt (Center for Economic Studies and ifo Institute (CESifo), 2007)
Intervening in the FX market implies a complex decision process for central banks. Monetary authorities have to decide whether to intervene or not, and if so, when and how. Since the successive steps of this procedure are likely to be highly interdependent, we adopt a nested logit approach to capture their relationships and to characterize the prominent features of the various steps of the intervention decision. Our findings shed some light on the determinants of central bank interventions, on the so-called secrecy puzzle and on the identification of the variables influencing the detection of foreign exchange transactions by market traders.
Keywords: E58; F31; G15; 330; Wechselkurspolitik; Reaktionsfunktion; Schätzung; Japan